Analisis Pemilihan Moda dari Mobil Pribadi ke Bus Trans Lampung di Bandar Udara Raden Inten II Lampung - Feby Aristia Putri (UNIVERSITAS LAMPUNG, 2019)
The purpose of this study is to identify factors that influence the choice of mode from private cars to Transs Lampung Buses and to analyze the selection model and can explain the probability of modal choice from private cars to Trans Lampung Buses, using random sampling techniques. The data was obtained through the results of the quisioner filler with binary logic method and PSPP analysis. Based on the results of the correlation test between the dependent variable and the independent variable, the Transportation Tool Used to Go to the Airport (X6), the Transportation Tool Used to Leave the Airport (X7) and the Trans Lampung Bus Leisure Consideration (X8) have a significance of 0,000; 0,000 and 0,041. This significance has a value of less than 0.05 which means that it correlates with the dependent variable. To find out the differences in the tendency of each vari - able that correlates can multiple linear regression equation Y = - 2.23 + 15.46 X6 + 13.48 X7 + 11.52 X8. Based on the probability test results of the 3 correlating variables produce scenario 1 the probability of a private car is 9.7% and the probability of Trans Lampung Bus is 90.3%. Scenario 2 generates 99% probability of private cars and the probability of Trans Lampung buses is 1%. Scenario 3 generates the probability of a private car of 8% and the probability of a Trans Lampung bus of 92%